YOSUA SANG PEPEMIMPIN: Implementasi Pola Kepemimpinan Yosua Dalam Kehidupan Bergereja Masa Kini - Yupe Usiel; Solideo Bole; Suarman Lase; Sylvia Natalia; Fransiskus Irwan Widjaja; Talizaro Tafonao (Sekolah Tinggi Teologi Injil Bhakti Caraka, 2022)
This research aims to understand Joshua’s leadership pattern that can be integrated into the churches today. In this writing, the author will discuss that a Christian leader is a person who has received a salvation from God through Jesus Christ, and he or she believes that God has called him or her with a responsibility, as a Christian leader which has the quality to integrate. The methodology in this research is qualitative. The author examined database using resources from articles, journals, books, and reliable literatures. The findings from this research that the model of Joshua’s leadership is kind, courage, integrated, innovative, and perseverance. Therefore, Joshua’s leadership is able to be implemented in every day’s aspect of life as a Christian as well as in development of education and technology.